A Staufen1-mediated decay pathway influences the local transcriptome in axons. Issue 2 (3rd July 2017) - Kim, Ju Youn; Deglincerti, Alessia; Jaffrey, Samie R.
ABSTRACT: Local translation is critical for diverse aspects of neuronal function, including mediating responses of elongating axons to guidance cues and other signaling molecules. A major determinant of the protein synthetic capacity of axons and growth cones is the specific set of mRNAs that are trafficked to these sites. However, recently it has become clear that the axonal transcriptome can also be shaped by local RNA degradation mechanisms, such as nonsense-mediated decay. Here we show that Staufen1-mediated decay can also occur within axons and mediate degradation of specific axonal transcripts. We show that Staufen1 and Upf1, which function together in Staufen1-mediated decay, are localized in growth cones. Selective depletion of Staufen1 from neurons results in a complex pattern of transcriptional alterations, with a subset of transcripts showing increased expression and increased RNA half-life consistent with their regulation by Staufen1-mediated decay. Additionally, we show certain transcripts, such as Rac1, are regulated by Staufen1 within axons and growth cones. The functional significance of Staufen1 in growth cones is supported by morphological alterations in growth cones following Staufen1 knockdown. Together these data point to Staufen1-mediated decay as a novel mechanism to control mRNA expression levels in axons and growth cones through local RNA degradation.